1960
DOI: 10.1152/ajplegacy.1960.199.6.1115
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm effects on contractility of the beating isovolumic left ventricle

Abstract: Variation in contractile force of the isovolumic contracting left ventricle of the dog was studied in open-chested in situ hearts. The electrocardiogram and intraventricular pressures were recorded at various heart volumes. Spontaneous changes in heart rate and rhythm occurred at all volumes. Isovolumic systolic pressure development (contractile force) varied with rate and rhythm. Contractile force increased with heart rate (treppe) regardless of pacemaker origin. When a premature beat was followed by a compen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…Cross-clamping of the aorta in three INTRODUCTION Mechanical alternans in isolated myocardium is said to result from an alternation in muscle fiber stretch (1) or from an alternation in the inotropic state of the muscle (2,3). Similarly, studies in pulsus alternans in the intact heart have shown this phenomenon to be both associated with (4)(5)(6) and independent of (7,8) alternations in ventricular filling or end-diastolic tension. The relative contribution of variations in contractile state and in initial fiber length, and tension to the pathogenesis of pulsus alternans in the intact heart is unknown since alternating beats have not been analyzed in terms of the myocardial length-tension-velocity relationship.…”
mentioning
confidence: 99%
“…Cross-clamping of the aorta in three INTRODUCTION Mechanical alternans in isolated myocardium is said to result from an alternation in muscle fiber stretch (1) or from an alternation in the inotropic state of the muscle (2,3). Similarly, studies in pulsus alternans in the intact heart have shown this phenomenon to be both associated with (4)(5)(6) and independent of (7,8) alternations in ventricular filling or end-diastolic tension. The relative contribution of variations in contractile state and in initial fiber length, and tension to the pathogenesis of pulsus alternans in the intact heart is unknown since alternating beats have not been analyzed in terms of the myocardial length-tension-velocity relationship.…”
mentioning
confidence: 99%
“…Also the frequency-dependent increase in the contractility decreased when the duration of stimulation was increased. The increase in cardiac contractility with an increase in the frequency of stimulation is well known (Katzung, Rasin & Scheider, 1957;Lendrum, Feinberg, Boyd & Katz, 1960;Blinks & Koch-Weser, 1961). The present results confirm our (Prasad & Kidwai, 1974) preliminary observation that electrical stimulation of isolated sarcolemmal fraction produces an inhibition of the sarcolemmal ATPase.…”
Section: Discussionmentioning
confidence: 97%
“…Alternation of end-diastolic volume has been considered an essential feature of mechanical alternans by some authors,6'5'6 but not by others. [8][9][10]17 On the basis of our findings, we suggest that in conditions of advanced LV disease or LV failure portions of the myocardium may contract with alternate strong or weak contractions in successive beats, while other portions of the ventricular myocardium contract with a discordant alternans or without any alternans. It seems reasonable to speculate that such discordant alternans would occur most often in patients with patchy involvement of the myocardium such as is seen in ischemic heart disease.…”
Section: Discussionmentioning
confidence: 97%